Teologi Bencana dan Rekonstruksi Etika Pembangunan (Perspektif Islam) - Triyanta, Agus (Unisia, 2016)
The following article investigates disaster of earthquake from Islamic ethics point of view. Disasteror earthquake constitute an active leaming that given by God by natural phenomenon in order to human introspect, human life in accordant with the urgent need of keeping universe, islam as a religion to give high motivation in order to answer the ultimate question and optimistic of life. Last but not least, it should be reconstruct religious ethical norms in term of human invironmental development. Happening disaster either as the God’s involvment or the rasionality of natural phenomenon.